Compulsory Conviviality in Early Modern England [with illustrations]. (12th September 2013) - Lemon, Rebecca
Abstract : To drink to a friend's health was the most popular and chronicled drinking ritual of the early modern period in England. While health drinking appears convivial in Cavalier poetry, such drinking was nonetheless controversial, heavily debated, and at times illegal. Furthermore, a host of writers, including Shakespeare, depict health drinking as compulsive and divisive. This essay traces the significant yet overlooked literature on health drinking, extending over an eighty‐year period from pamphleteers and playwrights of the 1580s–1610s through Cavalier poets up to the period of Charles II's restoration. This survey reveals thematic continuities running through the canon of healthing literature, as well as a significant shift in the literary representation of health drinking: a condemned practice reappears as a country ritual within the space of a generation. Whereas Elizabethan writers found national solidarity in satirizing healthing as a foreign and villainous practice, later Jacobean and Caroline poets use health drinking to establish political allegiances. But in doing so these poets become trapped in a mode of compulsory conviviality, and thus their verse resonates with an earlier generation's satirical views on the practice. (R. L.)